The Effects of Communication Efficacy on Information-Seeking Following Events That Increase Uncertainty: A Cross-Lagged Panel Analysis - Jang, Su Ahn; Tian, Yan (Published Online, 2012)
This study examined how past information-seeking experience influences individuals’ information-seeking decision process following an event that increases uncertainty in close relationships. To examine this issue, a two-wave, cross-lagged, panel-design study was conducted, and outcome expectancy, communication efficacy, and information-seeking were measured at each time. Analyses revealed that communication efficacy mediates the link between outcome expectancies and information-seeking under the conditions of uncertainty. The results also suggest that communication efficacy and information-seeking impact each other cyclically. The findings of this research suggest that scholars should focus on people's information-seeking experience and communication efficacy when examining information-seeking following events that increase uncertainty in close relationships.
Full text
Keywords: Close Relationships, Communication Efficacy, Information-Seeking, Uncertainty